2002
DOI: 10.1074/jbc.m109416200
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characteristics of the Mitochondrial Permeability Transition in Plants

Abstract: The behavior of purified potato mitochondria toward the main effectors of the animal mitochondrial permeability transition has been studied by light scattering, fluorescence, SDS-polyacrylamide gel electrophoresis, and immunoblotting techniques. The addition of Ca 2؉ induces a phosphate-dependent swelling that is fully inhibited by cyclosporin A if dithioerythritol is present. Mg 2؉ cannot be substituted for Ca 2؉ but competes with it. Disruption of the outer membrane and release of several proteins, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 76 publications
(78 reference statements)
7
103
1
1
Order By: Relevance
“…The system that regulates MPT in a Ca 2ϩ -independent manner has not been identified in plants to date. In contrast, Ca 2ϩ -mediated MPT has been reported in the mitochondria of several plants: swelling is induced in wheat mitochondria and potato tuber mitochondria by treatment with high concentrations (2.5-5.0 mM) of Ca 2ϩ in the presence of inorganic phosphate (15,16). However, we found that the properties of the swelling described in those studies are different from those of cannabinoid-treated mitochondrial swelling.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…The system that regulates MPT in a Ca 2ϩ -independent manner has not been identified in plants to date. In contrast, Ca 2ϩ -mediated MPT has been reported in the mitochondria of several plants: swelling is induced in wheat mitochondria and potato tuber mitochondria by treatment with high concentrations (2.5-5.0 mM) of Ca 2ϩ in the presence of inorganic phosphate (15,16). However, we found that the properties of the swelling described in those studies are different from those of cannabinoid-treated mitochondrial swelling.…”
Section: Discussioncontrasting
confidence: 55%
“…These results suggested that CBCA and THCA mediate cell death though MPT in Cannabis leaves. Mitochondrial Swelling and ⌬⌿m Reduction by Cannabinoids-Like animal MPT, plant MPT is also considered to be triggered by opening of MPT pores, leading to mitochondrial swelling and loss of mitochondrial membrane potential (⌬⌿m) (16). Therefore, we examined whether CBCA and THCA induce such responses in Cannabis mitochondria.…”
Section: Identification and Characterization Of Cell Death Regulatorsmentioning
confidence: 99%
See 3 more Smart Citations